2015
DOI: 10.1155/2015/574329
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Contraceptive Adherence among Women Seeking Family Planning Services at Reproductive Health Uganda, Mityana Branch

Abstract: Poor adherence is one of the main causes of unintended pregnancies among women of reproductive age. The purpose of this study was to establish the predictors of contraceptive adherence. A total of 211 women were enrolled and interviewed while seeking family planning services at reproductive health Uganda facility. Binary logistic regression was used to analyze the association between adherence and the independent variables. Most of the respondents (83.4%) were currently using a hormonal contraceptive. Of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
21
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
9
21
2
1
Order By: Relevance
“…The male partner support also encouraged longer duration of contraception as well as longer birth interval in this study similar to a study which reported that lack of male partner support is a factor in birth interval less than two years (25). Among female adolescent family planning clinic attendees in the US, partner awareness was 77.1%, 92.2% had the male partner's support and influence on decision for contraceptive use was male partner in 21.8% with highest likelihood of continuation related to mother and partner support (26).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The male partner support also encouraged longer duration of contraception as well as longer birth interval in this study similar to a study which reported that lack of male partner support is a factor in birth interval less than two years (25). Among female adolescent family planning clinic attendees in the US, partner awareness was 77.1%, 92.2% had the male partner's support and influence on decision for contraceptive use was male partner in 21.8% with highest likelihood of continuation related to mother and partner support (26).…”
Section: Discussionsupporting
confidence: 87%
“…The role of the male partner in discontinuation of previous and current contraception use brings to the fore reasons for discontinuation apart from pregnancy related issues. A report from Uganda showed that 43% of the women discontinued contraception for reasons other than pregnancy including male partner's resistance (25). …”
Section: Discussionmentioning
confidence: 99%
“…Both of these ndings are different from the results shown in previous studies [16,17]. Muhindo et al, in 2015, reported that lower education level was an indicator for poor contraceptive adherence in Uganda [16] and Mahumud et al, in 2015 reported that signi cantly higher rates of discontinuation were pronounced among married Bangladeshi women who were less educated [17]. These new results could consequently be due to the presence of the health workers who provided thorough and personal counselling to each participant during the study implementation period by making all the women, especially the less privileged ones, well aware that some side effects would be apparent as a result of being on the pill.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, women in the intervention group, from families with high monthly expenditure (20,000 + BDT, equivalent to USD 235+) also showed signi cantly higher discontinuation rates in comparison to women from other expenditure brackets in both groups. Both of these ndings are different from the results shown in previous studies [16,17]. Muhindo et al, in 2015, reported that lower education level was an indicator for poor contraceptive adherence in Uganda [16] and Mahumud et al, in 2015 reported that signi cantly higher rates of discontinuation were pronounced among married Bangladeshi women who were less educated [17].…”
Section: Discussionmentioning
confidence: 64%
“…This information also indicates the type of media most frequently accessed by women for family planning. Women prefer media with messages based on audio (radio) or a combination of visual and audio (television) [28][29][30] . This information is useful for policymakers or family planning activists to better utilize the two media categories as a medium for delivering messages about family planning.…”
mentioning
confidence: 99%